PENINGKATAN KETERAMPILAN BERBICARA SISWA MENGGUNAKAN MEDIA GAMBAR DI SEKOLAH DASAR NEGERI 17 RANTAU - Sauni, Sauni; Halidjah, Siti; Sugiyono, Sugiyono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe aim of this research  was to increase skill converse on grade II SDN 17 Rantau. This research uses descriptive method  with form of class action research and collaborative. The place of research took place at primary school of 17 Rantau, with research subject that is student of class II which amounted to 20 people. Data collecting tecnique used direct observation technique with data collecting tool that is IPKG I and IPKG 2 sheets. This research is done for 3 cycles. The result of the design of learning implementation obtained on average in the first cycle of 2,87, cycle II of 3,10, cycle III of 3,89. Result of research form learnig implementation got average score in cycle I equal to 2,66, cycle II equal yo 3,20, cycle III equal 3,78. Result of research from student speaking skill obtained average score in cycle I equal to 64,44, cycle II 77,22, cycle III equal to 92,78. Total number of students in cycle I reached 13 people and increase with completeness reach 16 people, in cycle III also increase amount mask as many as 20 people. From the data obtained can be concluded that there is an increase in each cycle. Thus research using the image media in the learning of grade II  can improve student’s speaking skills. Keywords: Increasing, Speaking Skills, Image Media